Evaluation of External Factors In Utilization of Electronic Journals at Library of Brawijaya University - Tri Mega Asri (Program Pendidikan Vokasi Universitas Brawijaya, 2016)
This study aims to determine the external factors in the use of electronic journals at library of Brawijaya University. This study implements a quantitative approach and the method used is descriptive method. The data collection was done through observation and questionnaire distribution. Observation was done to get information about digital service activities. Then questionnaires were distributed to the users by applying random sampling technique and the result was made in the form of coding book. Next, interview was done to measure users’ satisfaction in using the service at the library. The findings show that users have enough interest and motivation in the use of electronic journal collections with a percentage of 64.21%. Additionally, in terms of the relevance of the work, 75% respondents state that the electronic journal collection is highly relevant as a source of learning and working for the users.